Categorization of early embryonic malformations in broilers by a new classification method combining light microscopy and high-resolution Episcopic Microscopy - Yuval Cinnamon; Natalia Slutsky; Maxim Quint; Olga Genin; Dalit Sela-Donenfeld (Poultry Science)
Hatchability rates in broilers pose a significant challenge in the poultry industry. Despite advancements in breeding and incubation technology, hatch rates remain suboptimal due to factors like genetics, egg management, environmental stress, nutrition, and breeder age. Understanding the mechanisms behind compromised hatchability is crucial for improving broiler production. Since the embryonic phase accounts for ∼40% of a broiler's lifespan, poor embryonic development significantly contributes to malformations and mortality, adversely affecting both hatching and post-hatching performance.The foundations for proper embryogenesis are established within the first days of incubation during the formation of the three-germ layers and onset of organogenesis. These early days are critical, as malformations acquired during this period may severely affect growth and development of both the embryo and the hatchling chick. However, understanding of the types and prevalence of early embryonic malformations in broiler eggs remains incomplete.Here we present a novel tool for categorizing abnormalities in 3-day-old broiler embryos through a standardized classification system. Systematic mapping of malformation types and severities was conducted using light microscopy combined with High-Resolution Episcopic Microscopy (HREM), resulting in a new 'malformation atlas.' This detailed atlas identified various abnormalities, including lethal defects, axis duplications, neural tube and cardiovascular malformations, growth retardation, and head malposition, many of which are difficult to detect in young stages with traditional methods.To validate this classification tool, we next analyzed the impact of various egg management practices, such as storage and incubation conditions, on malformation types and prevalence in embryos from young and old breeding flocks. The atlas revealed significant variations in the types and occurrences of malformations, influenced by flock age and egg managements.Our findings highlight the value of implementing a novel malformation categorization tool for systematic understanding of poultry embryology. This knowledge could help reduce malformations, enhancing hatchability and improving broiler production efficiency.